Effect of argon gas flow rate on properties of film electrodes prepared by thermal vacuum evaporation from synthesized Cu2SnSe3 source - Sabli, Nordin; Talib, Zainal Abidin; Mat Yunus, Wan Mahmood; Zainal, Zulkarnain; Hilal, Hikmat S.; Fujii, Masatoshi (AIP Publishing LLC, 2013)
This work describes a new technique to enhance photoresponse of metal chalcogenide-based semiconductor film electrodes deposited by thermal vacuum evaporation under argon gas flow from synthesized Cu2SnSe3 sources. SnSe formation with Cu-doped was obtained under higher argon gas flow rate (VA = 25 cm3/min). Higher value of photoresponse was observed for films deposited under VA = 25 cm3/min which was 9.1%. This finding indicates that Cu atoms inside the SnSe film were important to increase carrier concentrations that promote higher photoresponse.